(untitled) (Fiep Bulletin - online, 2015)
This article has as aim to reflect about the professional formation in Physical Education, based on the policy analysis about this theme, pointing the present worries and the perspectives for the future, through a bibliographic study. With the performed analysis we can see an already known model of reforming originated in a central government to a periphery of institutions and the teacher is once more cast aside in this process. The fragmentation and the dichotomy in these policies go towards the necessity of understanding Physical Education as a social and pedagogical practice and the teachers formation ruled by the presupposition of the unity between theory and practice, the social commitment of the professional and the collective and interdisciplinary work.